Deformation behaviour analysis of different offset rim under different loading using finite element method. (2020) - Saxena, Prashant; Jain, Varun; Pradhan, Sharad K.
Abstract: Finite element analysis was conducted to study the behaviour of the car wheel rim with different offset with different loading condition. The tire in the vehicle is supported by the rim. The wheel and its design and dimensions should be according to a specified tire. This paper, comparative research of different offset rims (positive, negative, or zero offsets) has been investigated under different boundary condition such as load, air pressure. The automobile rims have been designed by using modelling software CATIA and obey the manufacturer standard design and dimension of the vehicle wheel rims. Machine design is the most important factor of industrial operations is used to identify the industrial problem and maintain product quality. The design optimization reduces the risk of damage involved in the industrial process. In this research, ANSYS simulation software is used to identify the various types of forces and stress acting upon the rim. The research shows the use of two different type materials structural steel and aluminium. The final outcome of the overall analysis is present in the form of a graphical representation of maximum stress and maximum displacement at a different type of loading condition. It has been found that the positive offset wheel rim produced high-stress value at 1620 Nm. This concludes the positive offset rim is not good at the high moment. And the central rim and negative offset rim gives the best result. The central rim and negative offset rim has capability sand at a higher moment.